Risk Screening of Introduced African Catfish (Clarias gariepinus) (Burchell, 1822) in Sarawak Using the Fish Invasiveness Screening Kit (FISK v2) - KIAT, CHIN HAN; Khairul Adha, A. Rahim (UNIMAS Publisher, 2023)
African Catfish (Clarias gariepinus) is a popular non-native fish for aquaculture in Malaysia. The issues of nonnative fish species have not been much discussed despite general perception of the negative effects of the species on the native biodiversity. Therefore, this study was conducted to estimate the possible risk of C. gariepinus in Sarawak using a semi-quantitative system of Fish Invasiveness Screening Kit version 2 (FISK v2). There are 49 questions in FISK v2 assessment which was assessed by three independent assessors with fisheries knowledge in Sarawak. Threshold was set at 19.0. Descriptive Statistics using SPSS 25.0 was used to run FISK score from three assessors. Result shows that Clarias gariepinus was categorised as “very high risk”. Clarias gariepinus has a FISK score of 43.00 ± 1.00 with a certainty factor of 0.89 ± 0.08. Environmental and biological criteria, followed by the economic impacts for this species and the gaps in legislation and framework in Sarawak were discussed thoroughly. It can be concluded that this preliminary assessment might have indicate a sign of invasion of this non-native species to the local biodiversity. The tool could be more robust if more comprehensive data are included which eventually be useful to assist in decisions regarding future management of non-native species in Sarawak.